2016
DOI: 10.1186/s12906-016-1478-1
|View full text |Cite
|
Sign up to set email alerts
|

Antinociception of petroleum ether fraction derived from crude methanol extract of Melastoma malabathricum leaves and its possible mechanisms of action in animal models

Abstract: Background Melastoma malabathricum L. (family Melastomaceae) has been traditionally used as remedies against various ailments including those related to pain. The methanol extract of M. malabathricum leaves has been proven to show antinociceptive activity. Thus, the present study aimed to determine the most effective fraction among the petroleum ether- (PEMM), ethyl acetate- (EAMM) and aqueous- (AQMM) fractions obtained through successive fractionation of crude, dried methanol extract of M. malabathricum (MEMM… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
10
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 55 publications
1
10
0
1
Order By: Relevance
“…The participation of the opioidergic system in asiaticoside antinociceptive activity was evaluated via hot plate-induced nociception and 2.5 % formalin-induced nociception, as described by [45].…”
Section: Participation Of the Opioidergic Systemmentioning
confidence: 99%
See 2 more Smart Citations
“…The participation of the opioidergic system in asiaticoside antinociceptive activity was evaluated via hot plate-induced nociception and 2.5 % formalin-induced nociception, as described by [45].…”
Section: Participation Of the Opioidergic Systemmentioning
confidence: 99%
“…The involvement of the vanilloid system (TRPV1) was determined according to the procedures as conducted by [45]. A total of 36 mice (6 mice per group) were given vehicle (10 mL/kg, p.…”
Section: Participation Of the Trpv1-vanilloid Systemmentioning
confidence: 99%
See 1 more Smart Citation
“…Banerjee et al reported a significant reduction in pain severity and frequency of painful episodes, in patients who underwent alternative treatment with extracts rich in grape PAs, reported a significant reduction in the use of narcotic analgesics. The mechanism of action by which tannins act in the pain treatment is still poorly explained, but it is a reality [ 17 ]. In order to evaluate the effect of AERM in the treatment of pain, we performed experimental tests with formalin and tail-flick assays.…”
Section: Resultsmentioning
confidence: 99%
“…6 Roots were also used as a cough and asthma medicine. 7 Leaves extract of M. malabathricum reported has activity as an antioxidant, hepatoprotective agent, 3 antiinflammation, 8,9 antinociceptive, 10 antimicrobial, 11 and wound healing. 12 Extraction method can affect the quality and constituents of extracts.…”
Section: Introductionmentioning
confidence: 99%